Factors related to online shopping intention among young men in Kuala Lumpur - Zuhairah, Katmin (2017)
The purpose of this study is to investigate the relationship of perceived ease of use, perceived usefulness, product variety, pricing, product guarantee and subjective norm towards online shopping intention among young men in Kuala Lumpur. 384 sets of questionnaire were distributed using convenience sampling method. However, only 310 set of questionnaire were returned back. All questionnaire collected were usable with a response rate of 80.7%. The data collected were analyzed using Statistical Package for Social Science (SPSS) version 23.0. Then, reliability analysis, descriptive analysis and inferential analysis were conducted. Through the reliability analysis, all variables used in this study are reliable with the value of each variable exceeds 0.6 as suggested by previous researcher. Besides, this study found that all the independent variables significantly relationship with online shopping intention among young men in Kuala Lumpur (p < 0.01). Through the regression model (R = 0.771, R2 = 0.594), it indicated that 59.4% of online shopping intention among young men in Kuala Lumpur was influenced to all the independent variables. Online shopping intention among young men in Kuala Lumpur is influenced mostly by product variety. Next, the influence factors to online shopping intention among young men in Kuala Lumpur were followed by product guarantee, perceived usefulness, perceived ease of use, subjective norm and lastly pricing. In order to further improve this research, future research may conduct a qualitative research and added a number of appropriate variables. Knowledge of the factors influencing the intention to buy online among young men is useful for organizations to prioritize their resources such as investment and time with the most efficient and effective manner